2017
DOI: 10.1039/c7ra08272j
|View full text |Cite
|
Sign up to set email alerts
|

A high modulus hydrogel obtained from hydrogen bond reconstruction and its application in vibration damper

Abstract: The cross-linking network of the hydrogel can be rearranged by evaporation-swelling treatment, the obtained hydrogel possesses an excellent vibration absorption ability and high elastic modulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Nevertheless, the resilience of GEL-0.5 was still above 70% (from the first cycle) at a compressive strain of 90% and reached a stable and high value from the second cycle (>95%), as shown in Figure 5 B. Moreover, the stable hysteresis energy dissipation of GEL-0.5 could be attributed to both the dissociation of ionic and hydrogen bonds and the friction between polymer chains [ 38 , 39 ]. After the applied stress was removed, the sacrificial bonds were able to reform rapidly, and thereby restore the integrity of GEL-0.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the resilience of GEL-0.5 was still above 70% (from the first cycle) at a compressive strain of 90% and reached a stable and high value from the second cycle (>95%), as shown in Figure 5 B. Moreover, the stable hysteresis energy dissipation of GEL-0.5 could be attributed to both the dissociation of ionic and hydrogen bonds and the friction between polymer chains [ 38 , 39 ]. After the applied stress was removed, the sacrificial bonds were able to reform rapidly, and thereby restore the integrity of GEL-0.5.…”
Section: Resultsmentioning
confidence: 99%
“…For the E ′ of CDN-gels at 1 Hz ( E ′ 1 ), the E ′ 1 dropped drastically after the VSTO was added and then gradually increased from 400 to 700 KPa with the VSTO content. It was reported that the E ′ in the low frequency relates to the effective network chain density ( N ), which can be depicted as follows [ 38 ]: E ′ = λNRT , where λ is the hydrogel-based constant and R and T are the gas constant and absolute temperature, respectively. For the CDN-gels with VSTO, the increased E ′ can be explained by the increase in the effective network chain density with VSTO content, while the drastic decrease of E ′ after the VSTO was introduced could be attributed to a change in λ , which reflects a large change in the flexibility of molecular chains.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, many researchers have studied the effect of various fillers on physical properties of SPEs, but most studies have focused on only ionic conductivity, and few works have been done on the mechanical stability. From the knowledge learned from the structural supporter of cell (extracellular matrix), the concrete reinforced with iron bars, and from several research papers expecting that one dimensional fillers enhance the mechanical stability of polymer, we expect to see an increase in the mechanical stability of chitosan‐based SPEs when nanowires are added as fillers instead of nanospheres. For a rigorous study on the dependence of mechanical stability on the shape of fillers used in chitosan‐based SPEs, two solutions each containing a different shape of filler (nanowires and nanospheres) should be prepared under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the case of chitosan‐based SPEs containing fillers (silver nanospheres or nanowires), the mechanical properties are stable even if 0.4 mL of glycerol is added. As shown in Figure (a), which is the graph showing the averaged elastic modulus as a function of the volume of glycerol, the elastic modulus of chitosan‐based SPEs containing silver nanospheres (asterisks in Figure (a)) and nanowires (black circles in Figure (a)) is approximately 4 MPa, that is approximately 40 times stronger than that of general hydrogels …”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonding can improve the mechanical properties of hydrogels. In contrast with covalent bonding, the strength of individual hydrogen bonding interaction was relatively weak, but the synergistic interactions among hydrogen bonds could produce strong interactions even over covalent bonding [31]. The composite hydrogels based on hydrogen bonding between polyacrylamide and bacterial cellulose were reported to exhibit good tensile with a breaking elongation of 2200% and a breaking stress of 1.35 MPa [32].…”
Section: Introductionmentioning
confidence: 99%